Update of model to predict sensible heat loss in broilers - Dos Santos, Marcos José Batista [UNESP]; Sakomura, Nilva Kazue [UNESP]; Pereira Da Silva, Edney [UNESP]; De Paula Dorigam, Juliano César [UNESP]; Maia, Alex Sandro Campos [UNESP] (CSIRO Publishing, 2017)
The present study was conducted to adjust and adapt some parameters of the model of production and heat loss by convection and conduction, so as to predict the actual feed intake (aFI) of broilers reared in sheds. The re-parameterised models were the sensible heat loss by convection from surface (HS) and by conduction (HC) in birds. The HS model was re-parameterised to calculate the heat loss of poultry reared in sheds and the parameters of thermal resistance of feathers (RF) and skin (RS) of poultry were inserted. The HC model was re-parameterised for birds in sheds and the RF, RS and the thermal resistance of the litter (R) were inserted. The re-parameterised HS model was HS ≤ [A × QV × (TB - TA)]/[(TB - 17) × (RF + RS)], where TA is the air temperature, QV is the volume factor, TB is the surface temperature of the bird (°C) and A was estimated to be 11.94 watts (W). The values found in the model ranged from 0.75 W for birds with 100 g BW subjected to 33°C TA, 50% HU, 0.1 m/s wind speed (V) and 12.53 W for birds with 4100 g subjected to 33°C TA, 80% HU and 0.1 m/s V. The values found in the re-parameterised HC model (HC ≤ [(TB - TC) × k × AR × QA]/[L × (RF + RS + R)], where K is the thermal conductivity of the litter, AR is the contact area of bird with the litter and QA is the area factor, and L is the litter height) ranging from 0.017 W to chickens with 100 g BW in comfortable conditions and 0.17 W for birds with 4100 g in thermal discomfort condition. The present study showed that the re-parameterisation of heat-loss equations is more accurate to predict the heat flux in broilers under different environmental conditions.
Keywords: environmental variables; heat loss; mathematical model